PEMBUATAN PROGRAM APLIKASI REGISTRASI KOLEKSI MUSEUM RADYAPUSTAKA BERBASIS WEB - Firdah Sholihah; Ery Dewayani; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
Application program of collection registrasion is to help employees or museum administrators to manage storage of data on a collection of objects that enter or registered, where the data is stored properly and computerized.The methodology used in the making of this application program is using waterfall method, where the method consists of the Planning Phase, Analysis Phase, Design Phase and Implementation Phase. The results achieved in this application program is the collection management activities can be run well and stored collections can be searched based on name of the collection, category of collection, storage areas and collection of contributor.